Fresno County Bar Association's Annual Judges' Dinner at Bob Crossland's Barn - Watkins, Howard::::::::: (1982)
Check-in table: Vickie Savaria, Val Weston, Rick Jensen, Eliot Nahigian, Lee Jacobson, Hon. Robert Martin wearing sunglasses, Hon. Pauline Davis Hanson